PENTINGNYA EXTERNAL FACTORS UNTUK KEUNGGULAN BERSAING INDUSTRI ENERGI BARU TERBARUKAN - Doni Purnama Alamsyah (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2016)
ABSTRACKRenewable Energy Industry in Indonesia is an important concern now, where government supports as external factors play an important role. External factors are important in gain competitive advantages of Renewable Energy industry in Indonesia. Therefore, this research focused on the study of the theoretical review of the relationship between external factors and competitive advantage. Discussed the theory study with previous research in this qualitative research, is used to model the latest research at the Renewable Energy industry. Results of the study found the importance of external factors in the Renewable Energy industry in gain competitive advantage. Another thing to note in particular the Renewable Energy industry in Indonesia on external factors is the political, economic, social, and technological. Utilized of these factors are important in improving competitive advantage. While the things that need to be considered by the Renewable Energy industry in competitive advantage is quality, capable, position, profitability, management and corporate image. This study theoretically improvement of previous research, and recommendations to develop with empirical study in the next research for the Renewable Energy industry.Keywords: External Factors, Competitive Advantage, Renewable Energy.